Analisis Kondisi Sosial Ekonomi Petani Jambu Mete (Anacardium Occidentale L.) Di Kelompok Tani Hutan Paloil Tob Desa Silu Kecamatan Fatuleu Kabupaten Kupang - Maya Selan; I Nyoman W Mahayasa; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
This study was conducted to determine the technical aspects of cashew cultivation (Anacardium occidentale L.) in the Paloil Tob Farm Farmers Group in Silu Village, Fatuleu District, Kupang Regency and the socio-economic conditions of Cashew farmers. This researchwas conducted in the Paloil Tob Forest Farmer Group, Silu Village, Fatuleu District, Kupang Regency, which was conducted for 2 months, from February to March 2020. This research used survey methods with data analysis using descriptive qualitative and quantitative descriptive analysis. The data is processed using the formula of income analysis, farming contribution and R/C Ratioanalysis. The results showed that aspects of the cultivation of Cashew (Anacardium occidentale L.) in the Paloil Tob Forest Farmer Group had not been carried out properly, because aspects of cultivation such as irrigation, fertilization, thinning and pest control had not been carried out according to applicable technical rules. Amount of cashew trees (Anacardium occidentale L.) owned by farmers is 2,811 trees out of a total land area of 33.77 ha and the average age of cashew trees owned by farmers is 11 years. Amount production of Cashew seeds consists of two, namely 1,450 kg of cashew seeds and 44 kg of cashew nuts. The amount cost spent to produce Cashew seeds in the Paloil Tob Forest Farmer Group is Rp.4,990,000 with an average cost per farmer of Rp.151,212. Amount incomeis Rp. 32,520,000 with an average income per farmer of Rp.985,455. Contribution of cashew business income to farmers' income is greater than agriculture and non-agricultural businesses. Economically, the Cashew business in the Toboil Forest Farmers Group in Silu Village, Fatuleu District, Kupang Regency in 2019 is profitable because the results of the analysis show that the R/C Ratio value is greaterthan 1 whichis 7.51.